2018
DOI: 10.1177/2158244017753506
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, Cultural Beliefs, and Practices That Mitigate Suicide Risk Among African American Women Veterans

Abstract: Current Armed Forces members are more than twice as likely as members of the general population to die by suicide (Department of Defense [DoD] Task Force on the Prevention of Suicide by Members of the Armed Forces, 2010). Suicide is also the second leading cause of death among individuals in the U.S. Armed Forces (Bryan, Jennings, Jobes, & Bradley, 2012). Although efforts within the DoD and Department of Veterans Affairs (VA) have focused on understanding how to prevent suicide among Service Members and Veter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 34 publications
(43 reference statements)
1
14
0
Order By: Relevance
“…This theme was evident across seven articles. By conceptualizing their experience of mental illness within a religious framework, participants described their faith as facilitating a sense of meaning, purpose, and ability to cope with the associated difficulties of mental illness; these feelings reportedly stemmed from a recognition of God’s plan for the participant (Holliman et al, 2018; Oxhandler et al, 2018; Starnino, 2016; Starnino & Canda, 2014; Tuffour, 2020). Participants who contextualized their mental illness and suffering in religious teaching and belief reported enhanced self-understanding (e.g., discovering oneself through adversity, developing one’s understanding of Christianity), spiritual renewal (e.g., feeling stronger in faith and closer to God), and religious practice (e.g., increased prayer and church attendance; De Castella & Simmonds, 2013; Sherman et al, 2018; Starnino, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This theme was evident across seven articles. By conceptualizing their experience of mental illness within a religious framework, participants described their faith as facilitating a sense of meaning, purpose, and ability to cope with the associated difficulties of mental illness; these feelings reportedly stemmed from a recognition of God’s plan for the participant (Holliman et al, 2018; Oxhandler et al, 2018; Starnino, 2016; Starnino & Canda, 2014; Tuffour, 2020). Participants who contextualized their mental illness and suffering in religious teaching and belief reported enhanced self-understanding (e.g., discovering oneself through adversity, developing one’s understanding of Christianity), spiritual renewal (e.g., feeling stronger in faith and closer to God), and religious practice (e.g., increased prayer and church attendance; De Castella & Simmonds, 2013; Sherman et al, 2018; Starnino, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…These articles acknowledged that belief in a supportive God allowed for a positive means of coping with mental illness among Christians. A commonly reported belief was that God had a plan and purpose for each individual and would not subject them to difficulties that they could not overcome; this illustrates how participants used their relationship with God as a means to cope with the suffering associated with mental illness (Holliman et al, 2018; Lloyd & Hutchinson, 2022; Oxhandler et al, 2018; Sherman et al, 2018; Starnino, 2016; Starnino & Canda, 2014). Throughout the articles, the relationship with God was characterized as personal and comforting, where God is seen as an accessible and available social support and strength (De Castella & Simmonds, 2013; Lilja et al, 2016; Oxhandler et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Throughout our scoping review, we found that religion cultivated protective factors that in turn conferred resiliency to suicide. Some of which were cultivated intrinsically within the individual and others from belonging to a religious community (Dorsey Holliman et al, 2018). For example, intrinsic religiosity (IR; an orientation toward religion as a value in itself) is associated with lower levels of depression, greater resilience, better quality of life, and fewer suicide attempts (Al Eid et al, 2020; Mosqueiro et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The literature which explores why women join the military predominately focuses on establishing an understanding of subsequent behaviours, such as resilience in adversity (Brooke, Holliman, Monteith, Spitzer, and Brenner, 2018), transitioning from the military (Burkhart and Hogan, 2015;Demers, 2013) and homelessness (Hamilton, Poza, Hines, and Washington, 2012). Whilst these explore reasons for joining, this is usually in the context of the wider studies research aims and is limited in its ability to establish reasons that are not focussed on subsequent difficulties, for instance, establishing why someone joined, in the context of exploring their narratives of premature discharge (Dichter and True, 2015).…”
Section: Why Women Join the Militarymentioning
confidence: 99%
“…While Gaines recognises the difficulties women can face, she also highlights that women who choose to work in such places are more likely to be confident, self-motivated, strong and fearless, which enables them to feel that they can be successful in the environment (2017). These characteristics are often associated with those who join the military and help them meet the challenges of service life (Brooke et al, 2018;Gutierrez et al, 2013). Burkhart and Hogan (2015) focus only on women's experiences, and establish a wide range of reasons for enlistment into the armed forces, such as: "To Seek Opportunities", "Pursuing Adventure" or "Seeking Safety" (p. 114).…”
Section: Why Women Join the Militarymentioning
confidence: 99%